A NEW SPECIES OF XYLOCOPA (NANOXYLOCOPA) FROM BRAZIL (HYMENOPTERA, APIDAE) - GABRIEL A.R. MELO (Papéis Avulsos de Zoologia)
ABSTRACT Xylocopa bella sp. nov., the second known species of the subgenus Xylocopa (Nanoxylocopa) Hurd & Moure, is newly described from the Espinhaço mountain range, in the state of Minas Gerais, and the Chapada Diamantina, in the state of Bahia, in eastern Brazil. It differs from X. ciliata Burmeister, the type species of X. (Nanoxylocopa), mainly by the possession, by females, of pale hairs intermixed with the black pubescence on the head and metasoma, the more abundant pubescence on mesoscutum and the much denser tergal pilosity, and the possession, by the male, of weakly infumated wing membrane, entirely dark scape, a patch of finely plumose pubescence on the anterior corners of the mesoscutum, narrower face, and shorter distance between the lateral ocellus and the eye. Additionally, X. ciliata, previously known from Argentina, Uruguay, Paraguay and southern Brazil, is newly recorded from the state of Minas Gerais.